P600 Real-world clinical characteristics and therapeutic strategies in patients with moderate-to-severe Inflammatory Bowel Disease in Argentina: Data from the RISE AR study. (27th May 2021) - Lasa, J S; Sambuelli, A; Zubiaurre, I; Correa, G J; Lubrano, P; Balderramo, D C; Ruffinengo, O; Brion, L; Leonardi, D B; El-Hakeh, J; Guimaraens, P N; Olivera Sendra, P
Abstract: Background: Evidence on the adoption of different pharmacologic strategies in inflammatory bowel disease (IBD) in the real-world setting in Latin America is scarce. Herein, we describe the clinical characteristics and therapeutic strategies of IBD patients (pts) in Argentina. Methods: RISE AR (NCT03488030) was a multicentre, non-interventional study with a cross-sectional evaluation and a 3-year retrospective data collection period conducted in Argentina (12/2018-05/2019) to assess the use of IBD treatments. Adult pts (≥18 years old) with a previous diagnosis of moderate-to-severe ulcerative colitis (UC) or Crohn′s disease (CD) based on clinical, endoscopic or imaging criteria at least 6 months prior to enrolment, were included. Results: Overall, 101 CD and 145 UC pts were included. Median (range) age (years) at enrolment was 39.5 (18.2–74.0) for CD (51.2% female) and 41.9 (18.0–80.4) for UC (55.2% female); median (range) disease duration (years) was 7.4 (0.6–36.9) for CD and 5 (0.7–33.8) for UC. At enrolment, 51.5% of CD pts had colonic involvement, 32.7% ileocolonic, 8.9% ileal, 1% isolated upper tract and 5.9% had combined L4/other. In UC, 46.2% had extensive colitis, 44.7% left-sided colitis and proctitis 9.1%. 51.6% of CD pts had non-inflammatory behaviour (37.7% stricturing; 13.9% penetrating), and 34% had perianal disease (13.9% as B1p), resulting in a total of 65.5% pts with complicated disease. Only 9.3% of CD (Harvey Bradshaw Index ≥8) and 7.7% of UC (partial Mayo Score ≥5) pts showed moderate-to-severe disease activity at enrolment. In CD, 70.3% of pts were receiving a biologic agent vs. 29.7% of UC pts. Immunosuppressant (IMM) use was similar between groups (CD 39.6%, UC 40.0%); nearly one-third of the pts on a biologic were receiving concomitant IMM (CD 33.8%, UC 34.9%). Aminosalicylates (5-ASA) were used for most UC pts (89.0%) vs. 47.5% of CD pts, mainly in those with L2 disease. 5-ASA monotherapy was prescribed in 32.1% of UC vs. 5.3% of CD pts, but were also used with IMM (UC 25%, CD 11%), biologics (UC 15%, CD 11.6%) or all three therapies combined (UC 6.4%, CD 17.9%). Corticosteroids (CS) were the least prescribed therapy (CD 7.9%, UC 13.8%). IBD treatments ever prescribed during the retrospective period were (CD, UC): biologics: 79.2%, 33.8%; IMM: 65.3%, 58.6%; 5-ASA: 62.4%, 97.9%; CS: 55.4%, 69.7%. Conclusion: In this cohort of IBD patients, biologics use was high, especially among CD patients, in line with disease behaviour, and possibly by their increased availability in these reference centres. This study also highlights country-specific clinical features such as the low proportion of CD pts and the high prevalence of colonic involvement in CD.